Exploring Oracle APEX for the University Data Analysis - Pastierik, Ivan; Kvet, Michal (2023 21st International Conference on Emerging eLearning Technologies and Applications (ICETA), 2023)
This paper delves into Oracle Application Express (APEX), a robust platform for web application development, showcasing its merits and suitability for creating a comprehensive Analytical Tool for University Data Management application. This application serves as an integrated solution to analyse various facets of university processes, such as student interactions, faculty engagement, study group dynamics, and subject performance, utilizing visual representations like graphs and charts. Beyond data analysis, the application also works as an Academic Information System, proficiently storing and managing student-centric information, including exam results and enrolled subjects. The initial sections of the paper explore the features and capabilities of Oracle APEX, highlighting its role as a low-code development platform that empowers developers to create sophisticated web applications with efficiency. The focal point of this study is the presentation of the Analytical Tool for University Data Management application created using Oracle APEX. By harnessing various modules and regions within Oracle APEX, the application offers a user-friendly interface that facilitates comprehensive data analysis. The application's ability to present individual and aggregate statistics through graphical visualizations empowers decision-makers with insightful information. The application holds great potential for future expansion utilising Machine Learning methods.